2019
DOI: 10.29328/journal.cjncp.1001012
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and views about coordinated individual planning from the perspective of active older adults

Abstract: Background: Today's older adults are often well informed and want to participate in decisionmaking processes. The coordinated individual planning process offers them active involvement in deciding and owning how their care will be managed. Aim:The aim of the study was to explore active older adults' knowledge and views regarding coordinated individual planning. Methods:The study has an exploratory inductive approach. Five focus-group discussions were conducted with 40 participants from different organizations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…This seemingly highlights the significance of consultation and collaboration between persons residing in nursing homes, and persons caring for them. Previous research involving older persons in the community setting has stressed the importance of partnership in care-planning and care delivery, as health care providers’ goals and priorities may not necessarily be in alignment with those of the individual ( Jobe, Engstrom, & Lindberg, 2019 ). With this in mind, staff and managers could use the findings from the present study to inform and enhance person-centered and person-directed care practices by maximizing opportunities for persons residing in nursing homes to be given options and choices, and the agency to make decisions where possible, in relation to their everyday care and living environment.…”
Section: Resultsmentioning
confidence: 99%
“…This seemingly highlights the significance of consultation and collaboration between persons residing in nursing homes, and persons caring for them. Previous research involving older persons in the community setting has stressed the importance of partnership in care-planning and care delivery, as health care providers’ goals and priorities may not necessarily be in alignment with those of the individual ( Jobe, Engstrom, & Lindberg, 2019 ). With this in mind, staff and managers could use the findings from the present study to inform and enhance person-centered and person-directed care practices by maximizing opportunities for persons residing in nursing homes to be given options and choices, and the agency to make decisions where possible, in relation to their everyday care and living environment.…”
Section: Resultsmentioning
confidence: 99%
“…This changed perspective is an important prerequisite for older person’s co-creation, which may uncover new or improved service opportunities. The study on CIP shows that many older people wish to be actively engaged in decisions regarding their care ( Jobe et al ., 2019 ). Another study by Engström et al .…”
Section: Discussionmentioning
confidence: 99%
“…This changed perspective is an important prerequisite for older person's co-creation, which may uncover new or improved service opportunities. The study on CIP shows that many older people wish to be actively engaged in decisions regarding their care (Jobe et al, 2019). Another study by Engstr€ om et al (2014) has shown that patients make different contributions to healthcare service development depending on the care setting (hospital vs. home), or if they are episodic or chronic patients.…”
Section: Realizing Patient Co-creationmentioning
confidence: 99%
See 1 more Smart Citation